Vaccine hesitancy and coercion: all eyes on France - Ward, Jeremy K.; Peretti-Watel, Patrick; Bocquier, Aurélie; Seror, Valérie; Verger, Pierre (Nature immunology, 2019)
With record levels of vaccine hesitancy, France faces the challenges of the contemporary crisis of trustin vaccines in a heightened form. For this reason, a closer look at its situation helps to highlight someoften overlooked factors behind the rise of vaccine hesitancy. The prevalence of hesitancy amongmedical professionals, and doctors in particular, is one of them. The changing landscape of vaccine-critical activism is another. The French context also underlines the limitations of the current toolsavailable to public health actors. As in many countries, traditional top-down communication effortshave proved unable to restore trust in vaccines. This led French public health authorities to concludethat extending the list of vaccines required for daycare and school entry was necessary to reachsatisfactory vaccine coverage. This extension of mandatory vaccination constitutes a live experimentto test the effectiveness of coercion in the so-called “post-truth era”. Where vaccine hesitancy is soprevalent, vaccine-critical arguments circulate widely and trust in public authorities is low, this type ofmeasure could polarize attitudes toward vaccines. There is a risk that the public health authorities willbecome complacent and rely upon coercion to do all the work. Coercive measures must be part of acomprehensive plan aimed at restoring trust in vaccines and not just at increasing vaccine coverage.The goal should still be to build a healthcare system immunized against doubts about vaccination